Inhibition of ROCK signaling pathway accelerates enteric neural crest cell‐based therapy after transplantation in a rat hypoganglionic model. Issue 9 (9th June 2020) - Zhao, Yuying; Ge, Xin; Yu, Hui; Kuil, Laura E.; Alves, Maria M.; Tian, Donghao; Huang, Qiang; Chen, Xinlin; Hofstra, Robert M. W.; Gao, Ya
Abstract: Background: Hirschsprung's disease (HSCR) is a congenital gastrointestinal disorder, characterized by enteric ganglia absence in part or entire of the colon, due to abnormal colonization and migration of enteric neural crest cells (ENCCs) during development. Currently, besides surgery which is the main therapy for HSCR, the potential of stem cell‐based transplantation was investigated as an alternative option. Although promising, it has limitations, including poor survival, differentiation, and migration of the grafted cells. We hypothesized that modulation of extracellular factors during transplantation could promote ENCCs proliferation and migration, leading to increased transplantation efficiency. Considering that the RhoA/ROCK pathway is highly involved in cytoskeletal dynamics and neurite growth, our study explored the effect of inhibition of this pathway to improve the success of ENCCs transplantation. Methods: Enteric neural crest cells were isolated from rat embryos and labeled with a GFP‐tag. Cell viability, apoptosis, differentiation, and migration assays were performed with and without RhoA/ROCK inhibition. Labeled ENCCs were transplanted into the muscle layer of an induced hypoganglionic rat model followed by intraperitoneal injections of ROCK inhibitor. The transplanted segments were collected 3 weeks after for histological analysis. Key Results: Our results showed that inhibition of ROCK increased viable cell number, differentiation, and migration of ENCCs in vitro. Moreover, transplantation of labeled ENCCs into the hypoganglionic model showed enhanced distribution of grafted ENCCs, upon treatment with ROCK inhibitor. Conclusions and Inferences: ROCK inhibitors influence ENCCs growth and migration in vitro and in vivo, and should be considered to improve the efficiency of ENCCs transplantation. Abstract : Enteric neural crest cells (ENCCs) were isolated from 14 days rat embryos, cultured into neurospheres, and labeled via GFP transduction. Inhibition of the ROCK pathway increased the viable cell number and growth, differentiation, and migration of ENCCs in vitro. Moreover, transplantation of GFP‐labeled ENCCs into the chemically induced hypoganglionic gut showed enhanced survival and expanded distribution of transplanted ENCCs upon treatment with ROCK inhibitor Y‐27632 in vivo.